(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: During severe inflammation of Covid-19, many inflammatory factors increase in body, and examining these factors can help to better understand the disease and predict expected risks. The present study aimed to investigate the association of CRP/Alb and the clinical outcome in patients with COVID-19. Material and Methods: This cross-sectional study on 315 patients with severe COVID-19 admitted in the intensive care unit (ICU) from April 1, 2020, to November 1, 2020. we collected and analyzed the serum inflammatory markers including C-reactive protein (CRP), albumin (Alb), CRP/Alb ratio, Erythrocyte sedimentation rate (ESR), and Red cell distribution width (RDW). The relationship of data was analyzed with the help of statistical analysis. Results: The results revealed higher levels of baseline ESR (P=0.007) and CRP (P=0.001), RDW (P< 0.001), and CRP/Alb (P<0.001) were significantly associated with prolonged hospitalization. Moreover, higher CRP/Alb was associated with an increase in in-hospital mortality. Conclusion: The CRP/Alb ratio and RDW can be used in routine clinical as a quick and easy measure to predict the mortality of COVID-19 patients.